2017
DOI: 10.1016/j.imbio.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increased heme oxygenase-1 on the lymphoproliferative response in dogs with visceral leishmaniasis

Abstract: Canine visceral leishmaniasis (CVL) is known to affect the cellular immunity of infected dogs, through impairing lymphoproliferation and microbicidal mechanisms. This study examined heme oxygenase-1 (HO-1) and its metabolites, oxidative stress and IL-10 levels in CVL and investigated correlations between these parameters. Additionally, the effects of HO-1 inhibition on the lymphoproliferative response and cytokine production in lymph node cells (LNCs) from infected dogs were evaluated. Forty-four dogs, 24 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 66 publications
4
17
1
Order By: Relevance
“…Recent studies have proposed that increased HO‐1 metabolism might be related to susceptibility to VL among humans and dogs . Similarly, we observed that induction of HO‐1 in macrophages from healthy dogs increased the infection rate and parasite load in these cells.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Recent studies have proposed that increased HO‐1 metabolism might be related to susceptibility to VL among humans and dogs . Similarly, we observed that induction of HO‐1 in macrophages from healthy dogs increased the infection rate and parasite load in these cells.…”
Section: Discussionsupporting
confidence: 83%
“…Not only was the percentage of infected human macrophages increased when these cells were treated with CoPP, but also the number of intracellular amastigotes and the viability of L. chagasi inside macrophages increased . It is reasonable to assume that the increase in HO‐1 metabolism observed in infected dogs that was recently described is one of the mechanisms responsible for the establishment and persistence of L. infantum infection in these animals. Corroborating this, our results demonstrated that induction of HO‐1 in macrophages from healthy dogs increased both the infection rate and the parasite load, such that there was even a positive correlation between these parameters and HO‐1 levels and gene expression.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Cellular stress by heme oxygenase-1, during L.chagasi infection has also been shown to be responsible for inflammatory imbalance 14 and inhibition of lymphoproliferative responses 15 thereby conferring disease susceptibility. Therefore, iron serves as double-edged sword- as a nutrient for pathogen and antimicrobial defense, becoming an important parameter in context of macrophage-residing Leishmania , determining the disease fate and how this balance is regulated by HPN has been a mystery in VL infection.…”
Section: Introductionmentioning
confidence: 99%